IL-12/15/18-induced cell death and mitochondrial dynamics of human NK cells - Terrén, Iñigo; Sandá, Víctor; Amarilla-Irusta, Ainhoa; Lopez-Pardo, Ainara; Sevilla, Arrate; Astarloa-Pando, Gabirel; Amo, Laura; Zenarruzabeitia, Olatz; Scorrano, Luca; Borrego, Francisco (Frontiers in Immunology, 2023)
Natural killer (NK) cells are lymphocytes with potent antitumor functions and, consequently, several NK cell-based strategies have been developed for cancer immunotherapy. A remarkable therapeutic approach is the adoptive transfer of NK cells stimulated with IL-12, IL-15 and IL-18. This cytokine stimulation endows NK cells with properties that resemble immunological memory and, for this reason, they are known as cytokine-induced memory-like (CIML) NK cells. Very promising results have been reported in clinical trials and yet, there are still unknown aspects of CIML NK cells. Here, we have conducted a preliminary study of their mitochondrial dynamics. Our results show that upon IL-12/15/18 stimulation the viability of NK cells decreased and an increment in mitochondrial superoxide levels was observed. In addition, we found that mitochondria appeared slightly elongated and their cristae density decreased following IL-12/15/18 stimulation, possibly in a process mediated by the low levels of optic atrophy type 1 (OPA1) protein. Interestingly, although mitophagy was slightly impaired, an increase in autophagic flux was observed, which might explain the reduced viability and the accumulation of unfit mitochondria. Our findings could be of relevance in order to design new strategies intended to improve the mitochondrial fitness of IL-12/15/18-stimulated NK cells with the aim of improving their therapeutic efficacy.